99 The healthy flint research coordinating centre: a community driven academic response to the flint water crisis. (19th September 2017) - Wallace, Kaneesha; Key, Kent; Lewis, E Yvonne; McKay, Athena; Carravallah, Laura; Furr-Holden, Debra; Corder, Keosha
Abstract : Statement of Purpose: To describe the creation of the Healthy Flint Research Coordinating Centre (HFRCC), a community-driven academic partnership, formed in response to the need to minimise fragmented and duplicative research efforts, increase community voice, and ensure ethical community involvement during the Flint Water Crisis (a public health crisis in which the entire community was exposed to and poisoned by dangerous lead levels in the drinking water). Methods/Approach: The HFRCC involves voluntary participation by community and researchers focused on the economic, environmental, behavioural and physical health of Flint residents; data dissemination; and training and education for academic and community partners. HFRCC services include: 1) Conducting community dialogues to gather community input on Flint-based needs; 2) A community ethics review board; 3) Hosting community-academic workshops; 4) Expanding the water crisis course; 5) An Open Data Flint repository; 6) A Flint Project Index; and 7) Hosting community driven research day. Results: During the first nine months, the HFRCC met bi-weekly and held five community dialogue sessions, four community-academic focused workshops; created a Flint-based project index; created a Centre website; launched Open Data Flint repository and interactive website. Approximately 150 individuals have attended HFRCC events. Currently, 17 datasets are in Open Data Flint. Conclusion: The HFRCC's work is community driven and focused and will pivot over time as the needs of the community change. Significance to Injury and Violence Prevention Science: Approximately 1 00 000 people in Flint were poisoned by lead contaminated drinking water. A speedy response to public health crises by local Universities and Community members/organisations to spread important information and provide key services is a model the HFRCC plans to apply to other communities.